PENGARUH KEBIJAKAN DIVIDEN DAN FAKTOR-FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Aleyda, Tanfidziah; Rinjani, Rinjani (E-Jurnal Akuntansi TSM, 2025)
The purpose of this research was to determine empirical evidence regarding the effect of dividend policies and other factors on company value. In this research, company value were measured by price to book value (PBV). This research used a sample of 147 data from 49 companies listed in the Manufacturing sector on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample selection in this research used purposive sampling and data analysis method used multiple linear regression analysis methods. The result on this study indicate that investment decision (TAG), profitability (ROA), institutional ownership (INST), and financial distress (FD) have an effect on company value. In addition, other independent variables, such as dividend policy (DPR) and firm size (UK) have no effect on company value.